Revitalizing Regional Landscapes, Redefining Peace: Satoyama and Satoumi as Models for Eco-Relational Justice in Japan - Navarro Caparrós, Raquel (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
The present article examines how the restoration of traditional landscapes through the practices of satoyama (a Japanese term referring to rural areas where humans and nature coexist, fostering biodiversity and cultural heritage) and satoumi (a Japanese term describing productive coastal areas that integrate human livelihoods with rich marine ecosystems) in Japan can serve as practical models for an ecological and relational conception of peace. Using an interdisciplinary approach that combines peace studies, ecological justice, and sustainable pedagogies, the article explores local efforts to revitalize the regional landscape after decades of environmental degradation. These efforts include community-led reforestation, sustainable management of water and agricultural resources, and the conservation of native species. The study of satoyama and satoumi in Japan demonstrates how these practices promote relational justice, extending beyond human conflicts to address the health of soil, water, and biodiversity. Furthermore, these models enable the integration of traditional knowledge and contemporary strategies, challenging dominant extractivist paradigms. It is argued that these initiatives foster ecological regeneration and enhance social cohesion by engaging multiple stakeholders—local governments, communities, and NGOs—in collaborative practices. The cases examined in this research, particularly the one of the Totoro Furusato Foundation, provide a concrete foundation for rethinking peace education from a sustainability perspective, bridging local and global dimensions of the ecological crisis.